PANDANGAN REMAJA TERHADAP PENDIDIKAN SEKS DALAM KELUARGA DI KELURAHAN TANGKERANG TENGAH PEKANBARU - Putri, Sukma eka putri Eka; Natuna, Daeng Ayub Natuna Ayub; Achmad, Said Suhil Achmad Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the perception of adolescent towards sex educationin the family at Tangkerang Tengah village, Pekanbaru . Formulation of the problem inthis research is how high the perception of adolescent towards sex education in the familyat Tangkerang Tengah village,Pekanbaru?.This is a descriptive study with a quantitativeapproach which aims to describe the result with figures. The sampling technique using aquota sampling technique, which is a technique for determining a sample of the populationthat have certain characteristics until the expectations of the amount of quota. Datacollection techniques in this study is by using a questionnaire, which was 56 statementitem. The data obtained from respondents who were 30 to sample the test and 89 for thestudy. After polling in the trial, there are six items that are not valid, and the researchersremoved one by one fact that is not, so the whole instrument reliably indicated byCronbach alpha = 0.96. The result of the data analysis shows that the perception ofadolescent towards sex education in the family from indicator sex differences between menand women relatively high with the value of mean 3.73 and Standard Deviation (SD) 0.74,compared with three other indicator that are the role of sex, the function and need of sex,and personal development. It means that the adolescent feel that sex education is related tosex differnces between men and women is very important for a parents to be given toadolescent.Keywords : sex education, adolescent, family